Philosophy of general teaching methods (Journal of Human Sciences, 2021)
The study aims to know the most important appropriate teaching methods in education, because of their greatness in the educational aspect and upon which the success of the learning process depends if the teacher chooses the appropriate method to communicate with his students and deliver information to them, and the research problem was formulated in the following questions: What is the concept of teaching methods?  What are the most important methods used in the teaching process?  What are the characteristics of Altris methods and their importance?  To answer these questions, we start from a main assumption: that teaching methods are a means of communicating ideas, information, skills and experiences from the professor to the student, meaning that they are a means of communication between the professor and the student, and that the teacher must choose the appropriate method from among the ways in which he transfers his information, or using  Two or several methods that fit the subject matter, taking into account the individual differences between learners and their levels, the research concluded that teaching methods need an appropriate environment for their application, such as providing a school environment in which all educational means are available, in addition to training learners on them to be skilled trainers in front of their students, as you need  Some methods are until the number of students is small so that the teacher can control the class, and you need to provide the appropriate time for each method.